Human Capital and Productivity: a Case Study of East Java - Sugeng Setyadi; Rizal Syaifudin; Deris Desmawan (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
This research examines the influence of level of education and health rate as the measurement of human capital to productivity in East Java Provice, during 2009 to 2015. Variable of level of education is measured by literacy rate, while the variable of health rate is measured by infant mortality rate. The panel data analysis is used as research method, which is Fixed Effect Model is the best model than the other models. The research results show that the variable of level of education is not significant to productivity, whreas, the variable healt rate has negative and significant influence to productivity. The reason is because educated worker is not really nedded in East Java Province. Some workers with skills and experiences are preferred. Therefore, in this research literacy rate cannot be used as good proxy to measured variable of level of education. Moreover, a decrease in infant mortality rate is indicating that the health rate is good. Hence, productivity